Xarifiid Copepods (Copepoda: Cyclopoida: Xarifiidae) Parasitic in the Coral Psammocora columna Dana, 1846 from Taiwan - Yu-Rong Cheng; Tsai-Ming Lu; De-Sing Ding (Animals, 2021)
A comprehensive knowledge of relationships between coral and coral-associated organisms is essential for the conservation studies of the coral reef community, yet the biodiversity database of coral-inhabiting copepods remains incomplete. Here we surveyed in a widely distributed scleractinian coral, Psammocora columna Dana, 1846, and newly discovered two endoparasitic copepod species, Xarifiayanliaoensis sp. nov. and Xarifia magnifica sp. nov. These two new species are described based on specimens collected in Taiwan, and they share several common morphological characters of Xarifia copepods, i.e., region dorsal to fifth legs having three posteriorly directed processes unequally. However, X. yanliaoensis sp. nov. is distinguishable from other species by the morphology of the endopods of legs, antenna, maxilla, and maxilliped (in both genders). The morphological characters of X. magnifica sp. nov. are the endopods of legs, leg 5, and maxilliped in the male. Including the two new species described in the present work, the genus Xarifia Humes, 1960 belongs to the cyclopoid family Xarifiidae Humes, 1960 currently consists of 94 species, and eight of them live in association with the Psammocora coral. A comparison table and a key to the species of Xarifia from Psammocora corals are given herein.